Aggregation of Somatia aestiva (Fabricius) (Diptera: Somatiidae) on leaves of Solanum stramonifolium Jacq. - Carvalho-Filho, Fernando da Silva (EntomoBrasilis, 2017)
Abstract. This study reports the first observation of many specimens of Somatia aestiva (Fabricius), drinking at same time the aqueous sugar solution produced by leaves of Solanum stramonifolium Jacq.(Solanaceae) in the Brazilian Amazon. Agregação de Somatia aestiva (Fabricius) (Diptera: Somatiidae) em folhas de Solanum stramonifolium Jacq. Resumo. Este estudo reporta a primeira observação de vários espécimes de Somatia aestiva (Fabricius) consumindo, na mesma ocasião, a solução líquida produzida por folhas de Solanum stramonifolium Jacq.(Solanaceae) na Amazônia Brasileira.